1994
DOI: 10.1179/cmq.1994.33.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of a Pilot Scale Iron Ore Pellet Induration Furnace

Abstract: In this work, a mathematical model of the pilot scale iron ore pellet induration furnace is presented. The validity of the model has been verified by performing separate experiments of subprocesses: drying, firing and cooling. The experiments were performed in such a way that the phenomena of heat transfer, drying and coke combustion could be studied separately. To do this, the green pellets were first dried, then heated to elevated temperatures at which the coke combustion commences and the pellet strength be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In order to obtain a strong optimisation and control of the industrial operations in ore sintering plants, different models were proposed and are available in the literature; many of those models refer to experiments performed on a laboratory scale. [31][32][33][34][35][36] In the present study, a model belonging to a multiobjective optimisation analysis has been carried out using data from an industrial plant. The recorded compositional values of the employed coals (wt-%) is shown in Table 1.…”
Section: Experimental Workflow Definitionmentioning
confidence: 99%
“…In order to obtain a strong optimisation and control of the industrial operations in ore sintering plants, different models were proposed and are available in the literature; many of those models refer to experiments performed on a laboratory scale. [31][32][33][34][35][36] In the present study, a model belonging to a multiobjective optimisation analysis has been carried out using data from an industrial plant. The recorded compositional values of the employed coals (wt-%) is shown in Table 1.…”
Section: Experimental Workflow Definitionmentioning
confidence: 99%
“…The review of literature on the present reactor scale models for the prediction of induration furnace performance reveals three important facts which are [9,[15][16][17][18][19][20][21]: (i) majority of these models are one-dimensional, (ii) models are based on topochemical reaction kinetics, (iii) models are concerned with induration of hematite pellets. However, recent studies have shown that the validity of these models is only limited to the diffusion control regime [22].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these properties, including the cold crushing strength, high‐temperature strength, reducibility, and extent of reaction are primarily the result of the sintering degree (bonding), phase content and distribution, porosity, and the pore size distribution in the pellets . Digitization of microstructural images enables the quantification of many of these features and further correlates the pellet properties empirically with the aid of reactor scale and statistical models . Models and software packages have been developed to determine features such as phase quantification and pore size distribution from microstructures, whereas none have been developed to determine the sintering degree.…”
Section: Introductionmentioning
confidence: 99%